Giving wings to her team : a novel about learning to coach the Toyota Kata way - Schwarz, Tilo; Liker, Jeffrey K. (Productivity Press, 2023)
Denise dreamed of being the kind of leader who empowered and engaged her people, but was becoming frustrated and disillusioned. Denise -- a fast-rising, young consultant at a large advisory firm -- lands a job as a manager in industry. Crisis strikes as low-cost competitors take market share and general chaos generates late shipments. Denise goes into Lean consulting mode but quickly learns her supervisors are not buying it. They're not engaged, and they find the Lean tools confusing and a distraction from their goals of getting product out. It's going to take some magic -- magic that's available to you, the reader, too! Come with Denise on a journey of discovery and skill development, as she moves beyond the tools and concepts of Lean and focuses on daily practice that helps her supervisors achieve their goals. It's about an approach called Toyota Kata that helps anyone develop and apply scientific thinking -- an exploratory mindset of curiosity and experimentation. A mentor from an unlikely place appears and shares with Denise how to coach her team. Once her supervisors dig into real problems they face every day, they begin to engage. Step by step, with insightful inputs from her mentor, Denise starts developing the skills to become a coaching manager. She watches her team meet their current challenges and be ready for more. When you teach and practice scientific thinking and coaching skills you give wings to your team, and new worlds of opportunity open up. If you're a manager you'll identify with how the team in this story goes beyond general preaching about best practices, to practicing how to get to where they want to be. If you're a Lean practitioner frustrated with applying tools with a limited half life, you'll learn how to develop people so they can achieve their most important goals and keep going. And if you're already a Toyota Kata practitioner, well ... you will love this book!